PENGARUH LATIHAN SENAM PRAMUKA DAN SENAM AYO BERGERAK INDONESIA TERHADAP TINGKAT KESEGARAN JASMANIPENGARUH LATIHAN SENAM PRAMUKA DAN SENAM AYO BERGERAK INDONESIA TERHADAP TINGKAT KESEGARAN JASMANI (Journal of Sport Coaching and Physical Education, 2016)
The level of the physical fitness of the council forces galang daughter junior high schools 22 semarang less than good. Problems research: 1 is there a gymnastic exercise pramuka influence on the level of the physical fitness ? , 2 ) is there influence a gymnastic exercise come on indonesia on the level of the physical fitness ? , 3 ) a gymnastic exercise which is better their influence ? Research objectives: 1 the influence of a gymnastic exercise pramuka on the level of the physical fitness , 2 ) the influence a gymnastic exercise come on indonesia on the level of the physical fitness , 3 ) a gymnastic exercise which is the better their influence. Research methodology uses the method eksperiment . Population were 20 students. An instrument tests using a physical health tests indonesia to live 13 to 15 years. The result showed the physical fitness of an average sample after do gymnastics scouts is as much as 31,45 % and after do gymnastics get a move on indonesia is about 24,8 % . Drawing conclusions the study: 1 there is the influence of a gymnastic exercise pramuka on the level of the physical fitness, 2 is the influence of a gymnastic exercise come on indonesia on the level of the physical fitness, 3 ) a gymnastic exercise pramuka better its effect on the physical fitness level.Advice of research: 1 do the second gymnastic before exercise pramuka, 2 ) do gymnastic routinely 3-5kali in a week, 3 to include activities gymnastics in the scouting.